Polymorphism -23HPhI in the promoter of insulin gene and pancreatic cancer: a pilot study - Krechler, T; Jachymova, M; Pavlikova, M; Vecka, M; Zeman, M; Krska, Z; Svestka, T; Zak, A (Neoplasma, 2009)
Pancreatic cancer (PC) is one of the most frequent gastrointestinal malignancies with extremely poor prognosis. In spite of a relative low incidence of PC, in comparison with other cancers, PC is the fourth leading cause of cancer death in USA in both sexes. The available data clearly suggest that diabetes mellitus (DM) can be both a long-standing cause of PC and an early manifestation of the disease. Besides of DM, insulin resistance and high insulin levels are linked as well with increased cancer risk, including PC. The variable number of tandem repeats (VNTR) locus upstream of the insulin gene (INS) regulates insulin expression and has been associated with susceptibility to many diseases including DM. It is known that there is nearly complete linkage disequilibrium of the insulin variable tandem of repeats (INS-VNTR) alleles I/III with neighboring -23 HphI A/T single nucleotide polymorphism (SNP) in Caucasians. Therefore, we have studied the association between SNP of -23HphI in promoter of INS with PC, DM Type 2 (2TDM) and healthy controls. In this study we investigated 153 subjects (86 M/67 F); 51 patients with newly-diagnosed PC (31 M/20 F), 45 patients with 2TDM (29 M/16 F) and 57 healthy control subjects (26 M/31 F). The polymorphism of -23HphI (A/T) in the promoter of INS was determined by the combination of polymerase chain reaction (PCR) with the restriction fragment length polymorphism (RFLP) methods. The results obtained by the PCR-RFLP analyses of SNP -23HphI were confirmed by a direct studied locus sequencing of the genomic DNA. The frequency of abnormal glucose metabolism (both DM and impaired fasting glucose) was 88 % (45/51) in PC group. The AA genotype in SNP -23HphI was more prevalent (67 % vs. 47 %; P<0.05) among PC patients compared to controls. Additionally, statistically significant differences were found in frequencies (%) of genotypes AA/AT/TT in groups with PC (67/27/6), 2TDM (53/40/7) compared to healthy controls (37/46/17) (P<0.05). Moreover, a statistically significant effect of -23HphI A/T polymorphism on tumor staging was found (P< 0.05). Polymorphism of -23HphI (A/T) in the promoter of INS may play a role in the pathogenesis of PC and could contribute to tumor staging. Key words: pancreatic cancer; insulin gene regulation; polymorphism of -23HphI; diabetes mellitus; disorders of glucoregulation.
Keywords: Polymorphism, Single Nucleotide; nádory slinivky břišní; Humans; Promoter Regions, Genetic; Polymorphism, Restriction Fragment Length; lidé středního věku; jednonukleotidový polymorfismus; Female; Aged; senioři; lidé; Minisatellite Repeats; minisatelitní repetice; pilotní projekty; Pilot Projects; Diabetes Mellitus, Type 2; staging nádorů; ženské pohlaví; Male; Pancreatic Neoplasms; Middle Aged; Insulin; Genetic Predisposition to Disease; genetická predispozice k nemoci; polymerázová řetězová reakce; Polymerase Chain Reaction; Neoplasm Staging; polymorfismus délky restrikčních fragmentů; mužské pohlaví; diabetes mellitus 2. typu; promotorové oblasti (genetika); inzulin